Methodic-praxеological approaches to the organization of self-educational activity of the subjects of education in the system of higher and postgraduate establishments - Бугра, Аліна Вікторівна; Коновал, Олександр Андрійович; Туркот, Тетяна Іванівна (Pedagogy of Higher and Secondary Education, 2017)
The article reveals the analysis of the content of methodic-praxеological approaches (competency building approach, activity-based approach, personcentered, acmeological, resource-based and reflective) to the organization of selfeducational activity of the subjects of education and proves the necessity of their implementation in the modern educational-information system of the higher educational establishment and of postgraduate establishments. Comparative analysis of its basic nature with traditional approach was done for deeper understanding of innovative entity of competence-based approach. According to activity-based approach different ways of independent work for students and different ways of control the providing of its productivity were proposed. There were set basic requirements to student-centered education that have to contribute to the success of students’ independent work. In the resource approach that foresees the providing of conditions for the most effective use and the fullest development of inner and outer resources of each student, the search of improving the effectiveness of management of students’ independent work was carried out. It was done due to the optimization of the combination of functions traditionally used learning tools and didactic means of new generation. It is pointed that the important result of realization of reflective approach is the formation students’ personal and professional quality such as autonomy. Analysis and synthesis of received experimental data allowed to outline directions of further scientific researches: introduction of the developed scientific-methodical system of organization and managing of students’ independent work in the process of studying much more scientific disciplines, its complex assessment taking into consideration the features of module-rating technology of education, the upgrade of suggested methodic-praxеological approaches of organization of self-educational activity in the practice of postgraduate education.